Comparative Efficacy of Different Repetitive Transcranial Magnetic Stimulation Protocols for Stroke: A Network Meta-Analysis - Xia, Yuan; Xu, Yuxiang; Li, Yongjie; Lu, Yue; Wang, Zhenyu (Frontiers in Neurology, 2022)
Background:Although repetitive transcranial magnetic stimulation (rTMS) has been proven to be effective in upper limb motor function and activities of daily living (ADL), the therapeutic effects of different stimulation protocols have not been effectively compared. To fill this gap, this study carried out the comparison on stroke patients' upper limb motor function and ADL performance by network meta-analysis. Methods:Randomized controlled trials (RCT) on the rTMS therapy for stroke were searched from various databases, including PubMed, web of science, Embase, Cochrane Library, ProQuest, Wanfang database, China National Knowledge Infrastructure (CNKI), and VIP information (www.cqvip.com).The retrieval period was from the establishment of the database to January, 2021.Meanwhile, 5 independent researchers were responsible for the study selection, data extraction, and quality evaluation.The outcome measures included Upper Extremity Fugl-Meyer Assessment(UE-FMA), Wolf Motor Function Test (WMFT), Modified Barthel Index (MBI), National Institute of Health stroke scale(NIHSS) and adverse reactions.Gemtc 0.14.3 software based on Bayesian model framework was used for network meta-analysis,and funnel plots and network diagram plots were conducted using Stata14.0 software. Results:95 studies and 5,016patients were included ultimately.The intervention measures included were: placebo, intermittent theta-burst stimulation (ITBS), continuous theta-burst stimulation (CTBS),1Hz rTMS,3-5Hz rTMS,and ≥10Hz rTMS. In the network meta-analysis results, different rTMS protocols were superior to placebo in terms of UE-FMA, NIHSS and MBI outcomes. In the probability ranking results,≥10 Hz rTMS ranked first in UE-FMA,WMFT and MBI. For the NIHSS outcome,the ITBS ranked first and 1Hz rTMS second. The subgroup analyses of UE-FMA showed that ≥10 Hz rTMS was the best stimulation protocol for mild stroke, severe stroke and convalescent phase, as well as ITBS for acute and subacute phases.In addition, it was reported in 13 included studies that only a few patients suffered from adverse reactions, such as headache, nausea, and emesis. CONCLUSION:Overall, ≥10 Hz rTMS may be the best stimulation protocol for improving upper limb motor function and ADL performance in stroke patients. Considering the impact of stroke severity and phase on upper limb motor function, ≥10 Hz rTMS may be the preferred stimulation protocol for mild, severe stroke and phase of convalescent and ITBS for acute and subacute phase.